Spirituality in health-care reform - Campbell, Courtney S. (Journal of religion and health, 1995)
Much of the discussion about health-care reform has focused on questions of political and economic policies. By contrast, this article contends that this dispute involves deeper questions of meaning regarding the kinds of values, including spiritual values, that we wish to be present in health care. Communities of religious believers have a civic duty of responsibility and a theological duty of stewardship for health-care institutions. Such communities bring to the health-care debate spiritual meaning embedded in themes of humility, justice, and mercy. These virtues provide a moral test of the soundness of reform proposals.